2020
DOI: 10.31575/jp.v3i3.183
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Kualitas Layanan, Kepercayaan Dan Promosi Terhadap Minat Nasabah Menabung Pada Bank Syariah Cabang Ulak Karang Kota Padang

Abstract: The survey conducted by Top Brand Indonesia obtained the latest data in 2016 indicates that the interest of saving customers at Bank Syariah Mandiri low is no exception in Bank Syariah Mandiri branch of Ulak Karang. It can certainly be influenced by various things, namely whether the quality of services provided by employees of Bank Syariah Mandiri is still less satisfactory, the promotion made by Bank Syariah Mandiri is still less attractive, and still decreased the level of customer confidence in Bank Syaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
2
7

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 0 publications
0
5
2
7
Order By: Relevance
“…The results of previous studies stated that brand trust has a positive and significant effect on the decision to choose a customer (Arif, 2020;Masitoh et al, 2018;Nasib, Syaifullah, & Daulay, 2021). However, this study is not in line with the research conducted by (Aziz & Hendrastyo, 2020) which stated that brand trust has no influence in increasing the decision to choose. The results of this study indicate that brand trust has a positive and significant effect on the decision to choose a mudharabah deposit product for Islamic Commercial Banks.…”
Section: The Effect Of Brand Trust On Choosing Decisionscontrasting
confidence: 94%
See 2 more Smart Citations
“…The results of previous studies stated that brand trust has a positive and significant effect on the decision to choose a customer (Arif, 2020;Masitoh et al, 2018;Nasib, Syaifullah, & Daulay, 2021). However, this study is not in line with the research conducted by (Aziz & Hendrastyo, 2020) which stated that brand trust has no influence in increasing the decision to choose. The results of this study indicate that brand trust has a positive and significant effect on the decision to choose a mudharabah deposit product for Islamic Commercial Banks.…”
Section: The Effect Of Brand Trust On Choosing Decisionscontrasting
confidence: 94%
“…Competition among the existing banking world experienced by government, private, conventional and Islamic banks is happening very rapidly (Aziz & Hendrastyo, 2020). All banks will offer various superior products and services in attracting new customers (Kartika et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the analysis in this study do not support the fifth hypothesis with the finding that trust has no significant effect on the Revisit Intention on sub-urban hospital. These results contradict several previous studies by Tanudjaya (2014;Saleem, et al 2017;Rizkiawan, 2019) but supported by the findings by Poon & Koay (2021;Isa et al, 2019;Arshad et al 2016;Aziz & Hendrastyo, 2019) which found that trust did not have a significant effect on revisit intention.…”
Section: Discussioncontrasting
confidence: 58%
“…2. Untuk mengatasi data yang tidak lengkap pihak akan bekerja sama dengan wali kelas untuk membantu mengkoordinir siswanya yang belum melangkapi data, lalu pegawai BTN akan melakukan kunjungan rutin setiap minggu untuk menerima kelengkapan data dan menerima bila ada setoran yang masuk (Aziz & Hendrastyo, 2020).…”
Section: Pendahuluanunclassified